2021
DOI: 10.3389/fncir.2021.784085
|View full text |Cite
|
Sign up to set email alerts
|

Temporally Targeted Interactions With Pathologic Oscillations as Therapeutical Targets in Epilepsy and Beyond

Abstract: Self-organized neuronal oscillations rely on precisely orchestrated ensemble activity in reverberating neuronal networks. Chronic, non-malignant disorders of the brain are often coupled to pathological neuronal activity patterns. In addition to the characteristic behavioral symptoms, these disturbances are giving rise to both transient and persistent changes of various brain rhythms. Increasing evidence support the causal role of these “oscillopathies” in the phenotypic emergence of the disease symptoms, ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 132 publications
0
8
0
Order By: Relevance
“…Similar positive effects were achieved in our study after only a single treatment procedure. This advantage permits us to consider a combination of resonance scanning with EEG-guided adaptive neurostimulation as a newly developed kind of oscillotherapeutics [ 22 , 23 ] that can effectively reduce stress and quickly produce the signs of cognitive rehabilitation in persons under exam stress via identifying neuronal network oscillations as potential therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%
“…Similar positive effects were achieved in our study after only a single treatment procedure. This advantage permits us to consider a combination of resonance scanning with EEG-guided adaptive neurostimulation as a newly developed kind of oscillotherapeutics [ 22 , 23 ] that can effectively reduce stress and quickly produce the signs of cognitive rehabilitation in persons under exam stress via identifying neuronal network oscillations as potential therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%
“…From both a clinical and basic-research perspective there is strong interest in acquiring a better understanding of how the timing of manipulations relative to endogenous oscillations and brain states impacts their effectiveness for treating psychiatric and neurological symptoms. By enhancing our knowledge of the precise impacts of phase-specific manipulations, we can inform how clinical stimulation strategies can complement, rather than compete with, the brain’s ongoing activity and improve these therapeutic interventions (Földi et al, 2021; Krause et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Oscillations arise from neuronal interactions that promote communication and information processing between regions of a functional neural network ( Engel et al, 2001 ; Buzsaki and Draguhn, 2004 ; Wang et al, 2020 ; Földi et al, 2021 ). Recent studies have shown that network oscillations temporally link neurons and enhance synaptic plasticity, supporting long-term information consolidation and is a cognitive process necessary for learning and memory ( Goltsev et al, 2013 ; Holmes, 2015 ; Sadaghiani and Kleinschmidt, 2016 ).…”
Section: Introductionmentioning
confidence: 99%